11th October: 20th Sunday After Pentecost - Candy, Julia (The expository times, 2015)
The article discusses an interpretation for passages from Job 23 and Psalm 22 in connection with the issue of stigmatization attitude towards depression. Cited are several mental health organizations and charities which consider social stigma as one barrier to helping people with depression. Offered is a discussion on the role of the Church in addressing stigma about depression.